2017
DOI: 10.1188/17.onf.e34-e41
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Cancer Survivorship Care Provided by Advanced Practice RNs Compared to Other Models of Care: A Systematic Review

Abstract: Incorporating descriptions of care models and associated outcomes into randomized, controlled trials of survivorship care would provide stronger evidence to guide practice. Studies evaluating outcomes of process/cost efficiency should be considered for future research. Outcome research is needed regarding the incorporation of SCPs into electronic health records.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…Post intervention completion, patients who had received the nurse-led survivorship care intervention had significantly reduced fatigue symptoms. Although a number of previous reviews have focused on nurse-led models of survivorship care [27,60,61], this is one of the first known metaanalyses of patient QoL outcomes after nurse-led survivorship care. The finding that nurse-led care provides a benefit to cancer survivors in terms of cognitive and social QoL is an important contribution which suggests cancer nurses can assist survivors adjust to life after treatment and nurse-led care results in reduced fatigue symptoms for cancer survivors in the longer term.…”
Section: Discussionmentioning
confidence: 99%
“…Post intervention completion, patients who had received the nurse-led survivorship care intervention had significantly reduced fatigue symptoms. Although a number of previous reviews have focused on nurse-led models of survivorship care [27,60,61], this is one of the first known metaanalyses of patient QoL outcomes after nurse-led survivorship care. The finding that nurse-led care provides a benefit to cancer survivors in terms of cognitive and social QoL is an important contribution which suggests cancer nurses can assist survivors adjust to life after treatment and nurse-led care results in reduced fatigue symptoms for cancer survivors in the longer term.…”
Section: Discussionmentioning
confidence: 99%
“…The Role of the APP Increasingly, as health care systems evolve to ensure quality and efficiency in care delivery, there is acknowledgment of the role for APPs in oncology care, with specific emphasis on the post-treatment period. 24,31,32 Our choice of NPs as one set of APPs to care for adult cancer survivors was built on a number of reports calling for nurses to practice at the top of their licenses and follows an Agency for Healthcare Research and Quality report that identified NPs as having "the right training and skills to address survivorship issues with patients." 33(p23) In addition, from a practical perspective, the choice of NPs as sole providers came from the institutional realization that it was important to free up the oncologists to see new patients and was part of the institutional plan to increase APPs in clinical care generally, especially in the outpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23] Although these reports outline the structure of the associated models, evaluation efforts, be they focused on the feasibility of implementation or the effectiveness of a particular model, have been limited. 24 To address this growing need for evaluation, this article describes one aspect of effectiveness evaluation: the concordance of care provided in APP-led survivorship clinics (in this case, NPs) with IOM guidelines for comprehensive survivorship care, among a sample of adult survivors at a single institution, Memorial Sloan Kettering Cancer Center (MSK; Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Eight systematic reviews were found that met the inclusion criteria for studies that assessed outcomes with SCP implementation compared with another intervention or usual care. 36,[60][61][62][63][64][65][66] The most recent systematic review (Hill et al 36 ) was the most comprehensive and included the majority of studies included in the earlier systematic reviews; therefore, it was retained for inclusion and its results are discussed in greater detail subsequently.…”
Section: Survivorship Cancer Plansmentioning
confidence: 99%